Aplicativo de realidade aumentada nos moldes ausubelianos para o ensino de orbitais atômicos - Almeida, Glaylton Batista de (2023)
Research has identified problems regarding understanding the chemical concept of Atomic Orbital, because this subject involves phenomena far from the student's reality and requires a visuospatial understanding of abstract models, which makes meaningful learning difficult. One of the ways mentioned by researchers to facilitate the learning process of this content is the use of digital technologies, since they have different ways of use, and can motivate students to make connections between the subject they want to understand with what they already have anchored in its cognitive structure, as advocated by the Meaningful Learning Theory (MLT). One of these technologies that has educational potential is Augmented Reality (AR), a feature that allows the integration of real-world objects with models created on computers. In view of this, the present work aims to develop and evaluate the usability of an AR application in the Ausubelian molds on the chemical concept of atomic orbitals. For this, the Recursive Software Development methodology was used. After the implementation of the application, research was started to validate the product with 17 subjects from the Degree in Chemistry course at Universidade Estadual Vale do Acaraú (UVA) and 17 from the Degree in Chemistry course at Faculdade de Educação de Crateús (FAEC) using the application, then responding to a system usability test through a Likert scale questionnaire. Among the main results, a score of 81.25 stands out, characterizing the software with an “A” grade and the adjective “excellent”, being within the acceptance standard, with a Net Promoter Score (NPS) “promoter”, in which the subjects would recommend the application to a friend. In addition, from a questionnaire applied after using the app, relevant data was obtained that shows that 94.11% of users believe that the application helps to understand what atomic orbitals are, while 85.3% believe that the RA facilitates in the process of this understanding. In view of this, the developed application can contribute to the teaching of atomic orbitals in Chemistry, since users presented good results in the learning questionnaire and evaluated the resource positively. The application will undergo adaptations and implementations according to the results obtained in the research its second version.